Continued smoking versus spontaneous quitting among pregnant women living in a high risk environment - Balázs, Peter; Grenczer, Andrea; Rákóczi, Ildiko; Foley, Kristie L (Central European Journal of Public Health, 2018)
OBJECTIVES: In Hungary, 37% of women living in poverty were smokers in 2012. There are no valid data of pregnant women's spontaneous smoking cessation. METHODS: Our retrospective cohort study (2009-2012) targeted the most underdeveloped regions with an estimated 6-8.5% of Roma population. The sample (N = 12,552) represented 76% of the target population i.e. women in four counties in a year delivering live born babies. Chi-square probe and multivariable logistic regression model (p < 0.05) were used to assess relationship between socio-demographic characteristics and spontaneous cessation. RESULTS: Prior to pregnancy, the overall smoking rate was 36.8%. That of women in deep poverty and Roma was 49.7% and 51.1%, respectively. 70.3% of smokers continued smoking during the pregnancy. Among them 80.6% lived in deep poverty. Spontaneous quitting rate was 23.0%. Factors correlated with continued smoking included being Roma (OR = 1.95), undereducated (OR = 2.66), living in homes lacking amenities (OR = 1.48), and having regularly smoking partner (OR = 2.07). Cessation was promoted by younger age (≤ 18 years) (OR = 0.18), being married (OR = 0.50), and the first pregnancy. CONCLUSIONS: Tailored cessation programmes are needed for Roma, older, low-income, and multiparous women who are less likely to quit on their own. Engaging husbands/partners is essential to reduce smoking among pregnant women and second-hand smoke exposure.
Keywords: Health Behavior; Smoking Cessation; retrospektivní studie; Risk Factors; chudoba; zdravé chování; Poverty; Pregnancy; těhotenství; Adult; dospělí; Smoking; Maďarsko; lidé; ženské pohlaví; Humans; odvykání kouření; rizikové faktory; Hungary; Retrospective Studies; Female; kouření